2014
DOI: 10.3892/or.2014.3447
|View full text |Cite
|
Sign up to set email alerts
|

Matrine alters microRNA expression profiles in SGC-7901 human gastric cancer cells

Abstract: Matrine, a major alkaloid extracted from Sophora flavescens, has been reported to possess antitumor properties in several types of cancers, including gastric cancer. However, its mechanisms of action on gastric cancer remain poorly understood. Dysregulation of microRNAs, a class of small, non-coding, regulatory RNA molecules involved in gene expression, is strongly correlated with cancer. The aim of the present study was to demonstrate that matrine treatment altered miRNA expression in SGC7901 cells. Using miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Matrine exerts excellent pharmacological activity and is beneficial for lowering body temperature, promoting diuresis, detoxifying, treating jaundice and preventing liver fibrosis. Previous studies indicated that matrine may be used as an effective treatment for various types of cancer, including liver (21) and lung cancer (22), gastric (23) and colon cancer (24), cervical cancer (25), leukemia (26), osteosarcoma (27), glioma (28) and nasopharyngeal carcinoma (29), and exhibits potent activity against various other types of cancer. Lung cancer occurs in the bronchial epithelium (30) and is characterized by a high morbidity rate (31), a considerable degree of malignancy, a great metastatic propensity in the early stages and the tendency to recur following tumor excision (32).…”
Section: Discussionmentioning
confidence: 99%
“…Matrine exerts excellent pharmacological activity and is beneficial for lowering body temperature, promoting diuresis, detoxifying, treating jaundice and preventing liver fibrosis. Previous studies indicated that matrine may be used as an effective treatment for various types of cancer, including liver (21) and lung cancer (22), gastric (23) and colon cancer (24), cervical cancer (25), leukemia (26), osteosarcoma (27), glioma (28) and nasopharyngeal carcinoma (29), and exhibits potent activity against various other types of cancer. Lung cancer occurs in the bronchial epithelium (30) and is characterized by a high morbidity rate (31), a considerable degree of malignancy, a great metastatic propensity in the early stages and the tendency to recur following tumor excision (32).…”
Section: Discussionmentioning
confidence: 99%
“…For example, matrine significantly reduces the overexpression of miRNA-21 and stimulates apoptosis in HepG2 and Hep3B cells [130]. Matrine also downregulated 14 miRNAs and upregulated their target genes in the MAPK signaling pathway in SGC7901 human gastric cancer cells [131]. Another natural compound, oxymatrine, acts on human ovarian cancer OVCAR3 cells by upregulating miR‑29b, which downregulates the expression level of matrix metalloproteinase‑2 and induces apoptosis [132].…”
Section: Apoptosis In Mdr Cells Through Modulation Of Microrna (Mimentioning
confidence: 99%
“…Oncogenic miRNAs block the function of certain mRNAs, of tumor suppressors whereas tumor suppressive miRNAs produce an anti-tumor effect [10, 11]. Several studies have reported that miRNAs can regulate several aspects of human gastric cancer pathogenesis, including metastasis, invasion, and self-renewal by targeting the EGR2 [12], MAPK [13] and PI3K/AKT signaling pathways [14]. Therefore, targeting specific miRNAs could be a possible alternative for the treatment of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%